Information technology. Local and metropolitan area networks. Token ring access method and physical layer specifications. Recommended practice for use of unshielded twisted pair cable (UTP) for token ring data transmission at 4 Mbit/s. (15th October 1993) - British Standards Institution,
No abstract available